Upaya Pencegahan Covid-19 di Padukuhan Jomblang Kalurahan Sendangadi Kapanewon Mlati Kabupaten Sleman DI Yogyakarta - Mursyid Mursyid; Muhammad Isnaini Fathoni; Yulianto harinugroho; Andhina Ika Sunardi; Wilis Fahlefi; M.F. Albashori; Hidayatullah Hidayatullah (Humanism: Journal of Community Empowerment (HJCE), 2022)
Covid-19 has been declared a world pandemic by WHO and has been designated by the Government as a non-natural disaster in the form of a disease outbreak that requires integrated countermeasures including the involvement of all components of society. The purpose of this community service activity is to find out the efforts made to prevent the spread of Covid -19 in RT. 004 RW 029 Padukuhan Jomblang, Sendangadi Village, Mlati district, Sleman Regency, DI Yogyakarta. The implementation of this Community Service activity is packaged using cooperative learning methods including lectures, discussions and practice. Efforts to prevent the spread of Covid -19 include: 1) Applying how to prevent the spread of Covid-19 in daily life; 2) Avoid direct contact with other people, and try not to leave the house except in critical times; 3) covid-19 is a virus that damages the respiratory system and can cause several complications from infection to death; and 4) Don't feel too stressed and burdened during this pandemic, because what is needed is a strong immune system or body metabolism and can increase immunity by exercising and eating healthy foods.